Using intervention mapping to facilitate and sustain return-to work after breast cancer: protocol for the FASTRACS multicentre randomized controlled trial - Fassier, Jean-Baptiste; Guittard, Laure; Fervers, Béatrice; Rouat, Sabrina; Sarnin, Philippe; Carretier, Julien; Broc, Guillaume; Letrilliart, Laurent; Péron, Julien; Lamort-Bouché, Marion (BMC cancer, 2024)
Background Women with breast cancer face many barriers to return to work (RTW) after their cancer. The main objective of the FASTRACS-RCT is to evaluate the impact of the FASTRACS (Facilitate and Sustain Return to Work after Breast Cancer) intervention on the sustainable RTW of breast cancer patients, 12 months after the end of active treatment. Methods FASTRACS-RCT is a prospective, national, multicentre, randomized, controlled and open-label study. A total of 420 patients with early breast cancer scheduled for surgery and (neo)adjuvant chemotherapy, will be randomly assigned (1:1 ratio) to: (i) the intervention arm comprising four steps over 6 months : Handing over the intervention tools; transitional medical consultation with the general practitioner (GP); pre-RTW visit with the company’s occupational physician (OP); catch-up visit with a hospital-based RTW expert (if sick leave > 10 months) (ii) the control arm to receive usual care. The design of the FASTRACS intervention was informed by intervention mapping for complex interventions in health promotion planning, and involved patients and representatives of relevant stakeholders. Specific tools were developed to bridge the gap between the hospital, the GP, the OP and the workplace: a toolkit for breast cancer patients comprising a theory-based guide; specific checklists for the GP and the OP, respectively; and a theory-based guide for workplace actors (employer, manager, colleagues). The primary endpoint will associate sustainable RTW (full-time or part-time work at 50% or more of working time, for at least 28 consecutive days) and days off work. It will be assessed at 4, 8 and 12 months after the end of active oncological treatment. Secondary endpoints will include quality of life, anxiety, depression, RTW self-efficacy, physical activity, social support, job accommodations, work productivity, job status, and the usefulness and acceptability of the intervention’s tools. Discussion FASTRACS-RCT will be supplemented by a realist evaluation approach aimed at understanding the influence of context in activating the intervention’s mechanisms and effects. If the expected impact of the intervention is confirmed, the intervention will be adapted and scaled-up for other cancers and chronic diseases to better integrate healthcare and work disability prevention. Trial registration NCT04846972 ; April 15, 2021.